Effect of growth regulators and spacing on multiplication of planting ullits in cardamom (Elettaria cardamomum Maton) - CHANDRAPPA, M THIMMARAYAPPA, S M SHANTHAVEERABHADRAIAH, H M (Journal of Spices and Aromatic Crops, 1997)
Experiments on multiplication of planting units in cardamom (Elettaria cardamomum) under uniform shade revealed that growth regulators (Etherel 250 ppm and Cycocel 2000 ppm) did not influence proliferation of planting units whereas closer spacing (0.9 m x 0.3 m) resulted in significantly higher number of planting units.